Neuropeptide Y in itch regulation. (December 2019) - Jakobsson, Jon E.T.; Ma, Haisha; Lagerström, Malin C.
Abstract: Itch is a somatosensory sensation that informs the organism about the presence of potentially harmful substances or parasites, and initiates scratching to remove the threat. Itch-inducing (pruritogenic) substances activate primary afferent neurons in the skin through interactions with specific receptors that converts the stimulus into an electrical signal. These signals are conveyed to the dorsal horn of the spinal cord through the release of neurotransmitters such as natriuretic polypeptide b and somatostatin, leading to an integrated response within a complex spinal interneuronal network. A large sub-population of somatostatin-expressing spinal interneurons also carry the Neuropeptide Y (NPY) Y1 receptor, indicating that NPY and somatostatin partly regulate the same neuronal pathway. This review focuses on recent findings regarding the role of the NPY/Y1 and somatostatin/SST2A receptor in itch, and also presents data integrating the two neurotransmitter systems. Highlights: The review covers current knowledge regarding the role of Neuropeptide Y in itch regulation The analysis shows that blocking Y1 increase scratching behavior induced by the somatostatin agonist octreotide